SIGNAGE JALAN PERMUKIMAN OBJEK STUDI : PERMUKIMAN BRAGA - Willyam J Ompusunggu; Yohannes B. Dwisusanto (Riset Arsitektur (RISA), 2022)
Abstract - Signage is one of the elements that form the face of the region, and is a medium of information at the micro and macro levels. Signs are an important item as a transmitter of information for observers, placing the sign correctly will have a very good effect as a source of information. The need for a system/signage to convey information in the form of signs that show the direction of getting better and developing, for crowds of people or masses who need information on directions. The information provided is experience, exposure, and knowledge of the area. Settlements that develop organically are widely spread across the most populous provinces in Indonesia. Braga settlement is located in the economic center of the city of Bandung, the organic settlement area has little information about the area, it is still scattered sporadically (only at the entrance in the form of a gate), not connected to one another in the area and there is no signage facility. Areas that do not have road information can turn into an unpleasant atmosphere and find it difficult to know the way for individuals to access the road for the first time, but people and people who are accustomed to accessing Braga residential roads have no difficulty in finding roads with object identification signs and elements that can be understood and understood. considered as signage. The purpose of using roads in residential areas is to provide alternative access to the other side of the city. This research is exploratory and uses qualitative methods, literature review, and conceptual proposals. Roads within the area can be an alternative way to go to different places, roads within the area have different entry and exit access, many branching alleys, and multi-story buildings inside. The area is confusing and difficult to orientate. Keywords: signage, street, visual, settlement, Braga Bandung